PENGARUH MODEL THINK PAIR SHARE-PROBLEM SOLVING TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN SELF-EFFICACY SISWA - Nina Soraya; Rusmansyah Rusmansyah; Maya Istyadji (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2018)
Abstract. The ability to think critically and understanding self-efficacy is the main thing of every learner should be have. One of the learning models that can combine critical thinking and self-efficacy is the Think Pair Share-Problem Solving learning model. The learnng model of TPS-Problem Solving is applied to students of class X MIA SMA Negeri 4 Banjarmasin on electrolyte and non-electrolyte solution concept. The aim of this research is to know the students' critical thinking and self-efficacy after being given the model of TPS-Problem Solving. The design of research used pretest-posttest nonequivalent control group and samples taken by purposive sampling technique. Technique of collecting data using test, that is critical thinking ability and questionnaire in the form of self efficacy questionnaire and student response. Data were analyzed by descriptive analysis technique and inferential analysis. The results showed that there were significant differences between critical thinking ability and self efficacy. The use of the TPS-Problem Solving learning model is more effective than the conventional model and the TPS-Problem Solving learning model gets a positive response from students. Keywords: think pair share, problem solving, critical thinking, self-efficacy